Conducting school surveys on drug abuse. (Global assessment programme on drug abuse, 2003)
"[T]he GAP Toolkit Module 3 has been produced to assist States Members of the United Nations to develop culturally appropriate systems, relevant to the countries concerned, for collecting drug information, to support existing drug information systems by promoting their conformity with internationally recognized standards of good practice and to focus on the harmonization of drug abuse indicators. GAP Toolkit Module 3 forms one component of a compendium of methodological guides on drug abuse epidemiology that have been developed to support data collection activities."--Preface